Yield Regulation in the Fuel Forests of Madras State - Wilson, J. (Indian Forester, 1962)
A brief description of the fuel forests in the Madras State is presented. In addition to the natural forests, the State has fuel plantations of Blue-gum, Wattle, Casuarina and other miscellaneous species. The objects of management of the fuel forests are listed. The development of working of the natural fuel forests as well as the plantations, the various si1vicultural systems adopted in the past and current practices are described with reference to regulating the yield. Other factors like assessment of out-turn and sale-value, considerations of market and utilisation are briefly described. The present scarcity of fuel in the State is great and is still increasing on account of the rise in population and the progressive reduction in yield in successive rotations in the dry fuel forests owing to mortality of stools and lack of natural regeneration. The measures proposed to make good the deficiency are briefly indicated.